The CORE model: An innovative strategy to strengthen students’ mathematical connections and problem-solving skills in junior high school - Apriyanti, Peni; Sumardi, Hari; Hanifah, Hanifah (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Developing students’ mathematical connection and problem-solving skills remains a persistent challenge in Indonesian secondary mathematics education. This study examined the impact of the CORE (Connecting, Organizing, Reflecting, Extending) instructional model on students’ mathematical connections and problem-solving abilities at SMPN 02 Kota Bengkulu. A quantitative approach with a controlled-comparison design was employed, and data were analyzed using Analysis of Covariance (ANCOVA) to assess the model’s effects while controlling for prior ability. The findings revealed that prior mathematical ability significantly explained 25.3% of the variance in students’ mathematical connection skills and 55.3% of the variance in their problem-solving performance. After implementing the CORE model, students demonstrated substantial improvement in both areas. The model accounted for 57.0% of the variance in mathematical connection ability, particularly enhancing students’ capacity to relate mathematics to other disciplines and real-life contexts, and 19.9% of the variance in problem-solving skills, especially in understanding problems, planning, and reviewing solutions. These results suggest that the CORE model effectively promotes cross-disciplinary integration, contextual understanding, and reflective reasoning in mathematics learning. Theoretically, the findings reinforce the role of constructivist and reflective learning frameworks in strengthening students’ higher-order thinking and meaningful engagement with mathematical concepts.